(untitled) (American Journal of Arts and Human Science, 2023)
Spirituality is a driving force that capacitates adolescents to overcome challenges and adversities and allows them to develop a sense of hope, meaning, and purpose. The study determines the level of spirituality of adolescents in South Central Mindanao, Philippines after the COVID-19 pandemic. A quantitative non-experimental method of research was utilized. The respondents were selected using a non-probability sampling technique. The study utilized an adapted, contextualized, and validated survey instrument. In analyzing the data, mean, standard deviation and Analysis of Variance were used. The results revealed that the level of spirituality of adolescents is very high. Furthermore, there is a significant difference in adolescents’ spirituality level when analyzed according to City.